2015
DOI: 10.1002/cssc.201403393
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Properties of 3D Binder‐Free Manganese Oxide Anodes by Preformation of a Solid Electrolyte Interphase

Abstract: Huge irreversible capacity loss prevents the successful use of metal oxide anodes in Li-ion full cells. Here, we focus on the critical prelithiation step and demonstrate the challenge of electrolyte decomposition on a pristine anode in a full cell. Both an electrochemical activation process (54 h) with Li metal and a new electrolytic process (75 min) without Li metal were used to preform complete solid electrolyte interphase (SEI) layers on 3 D binder-free MnOy -based anodes. The preformed SEI layers mitigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…23 Similar phenomena are also found in the silicon and metal oxide anode of Li-ion battery. 25,26 Recently, Tong et al 27,28 fabricated porous or hollow Al coated with a uniform carbon layer, which provided sufficient space to accommodate volume expansion. Moreover, the outer carbon layer buffered the volume variation effect and to form a passive SEI film during the Al-Li alloying.…”
mentioning
confidence: 99%
“…23 Similar phenomena are also found in the silicon and metal oxide anode of Li-ion battery. 25,26 Recently, Tong et al 27,28 fabricated porous or hollow Al coated with a uniform carbon layer, which provided sufficient space to accommodate volume expansion. Moreover, the outer carbon layer buffered the volume variation effect and to form a passive SEI film during the Al-Li alloying.…”
mentioning
confidence: 99%
“…It is well known that Li metal also consumes electrolyte reduction products during the cyclingi nt he conventional half-cell configuration, [32] which makes control of the prelithiation more difficult. [34] Hence, in this work, good controllability wasa chieved at ah igh mass-normalized current density (1 Ag Si À1 ), which makes big savings in the prelithiationtime. [7,33] In the electrolytic cell, the influence of the highly reactive Li metal on the SEI formation was excluded, which resulted in better controllability.…”
Section: à2mentioning
confidence: 87%
“…[7,33] In the electrolytic cell, the influence of the highly reactive Li metal on the SEI formation was excluded, which resulted in better controllability. [34] Hence, in this work, good controllability wasa chieved at ah igh mass-normalized current density (1 Ag Si À1 ), which makes big savings in the prelithiationtime.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…For the SEI layer, some studies revealed that the initial charge-discharge is sufficient to form the SEI layer and excessive lithiation leads to the loss of active materials and the formation of dendrites. [156][157][158] Based on this simple strategy, both pre-sodiation in SIBs [25] and pre-lithiation in LIBs [159] have achieved good electrochemical performance.…”
Section: Subsequently Liu Et Al Used This Rollmentioning
confidence: 99%